The local knowledge and potential of suweg (Amorphophallus paeoniifolius) in the Citanduy and Cimanuk watersheds of West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mutaqin AZ, Iskandar J, Irawan B, Suryana, Kurnadie D, Nurzaman M, Shanida SS. 2023. The local knowledge and potential of suweg (Amorphophallus paeoniifolius) in the Citanduy and Cimanuk watersheds of West Java, Indonesia. Biodiversitas 24: 370-378. The Indonesian archipelago is rich in natural resources and ethnic diversity. Each ethnic group interacts with the surrounding environment in ways that often differ. Interaction with the environment creates local knowledge that is complex in terms of language, practical understanding, beliefs, and social interaction. One useful natural resource that grows in many areas of Indonesia, especially in watershed ecosystems, is Suweg (the elephant foot yam) which has the scientific name Amorphophallus paeoniifolius (Dennst.) Nicolson. Local communities, such as in the Citanduy and Cimanuk watersheds of West Java, use suweg for various purposes in their lives. The study reported here aimed to document the local knowledge and development potential for suweg in the Citanduy and Cimanuk watersheds, West Java, Indonesia. The research used mixed observation methods, predominantly qualitative. The data collection technique was purposive, based on interviews (structured, semi-structured, and in-depth interviews) with several informants or community groups who were considered competent to know suweg. Data were analyzed through emic and ethical approaches. Data analysis was conducted by cross-checking, summarizing, and synthesizing. The results of the research showed that suweg grows in a range of environmental conditions on managed agroecosystem lands. The corms of suweg are peeled, cooked and eaten in a variety of side dishes. The leaves of suweg have been used as food for fish in pond-system aquaculture. The results of this study suggest that suweg has the potential for expanded development, based on sociological and ecological evidence.